2019
DOI: 10.1055/s-0037-1610859
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Synthesis of Fused Imidazopyrazine N-Oxide Skeletons

Abstract: N-Propargyl-2-aroylimidazoles synthesized and converted into the corresponding ketoximes. Under various conditions, several mono- and diketoxime imidazole derivatives were formed by converting the carbonyl or carbonyl and propargyl groups into oxime groups. N-Propargyl monooxime imidazole derivatives were cyclized by treatment with CuI to give various imidazopyrazine N-­oxides. Several copper salts, such as CuOAc, CuSO4, and CuOTf, formed the same cyclization product. This cyclization reaction occurred only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…In the first stage of the study, unconjugated ynone derivatives 2 were synthesized as starting compounds using ethyl benzoyl acetate derivatives according to the methods available in the literature. [22][23][24]32] The general procedure in high yield and ideal conditions were established (Scheme 1). The acidic CH 2 protons in ethyl benzoyl acetate derivatives was deprotonated with the appropriate base, propargyl bromide was added and synthesis of unconjugated ynone derivatives was carried out as starting compound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage of the study, unconjugated ynone derivatives 2 were synthesized as starting compounds using ethyl benzoyl acetate derivatives according to the methods available in the literature. [22][23][24]32] The general procedure in high yield and ideal conditions were established (Scheme 1). The acidic CH 2 protons in ethyl benzoyl acetate derivatives was deprotonated with the appropriate base, propargyl bromide was added and synthesis of unconjugated ynone derivatives was carried out as starting compound.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the cyclization of semi‐carbazide and unconjugated ynone derivatives as starting chemicals for the synthesis of new substituted pyrrole derivatives was investigated. In the first stage of the study, unconjugated ynone derivatives 2 were synthesized as starting compounds using ethyl benzoyl acetate derivatives according to the methods available in the literature [22–24,32] . The general procedure in high yield and ideal conditions were established (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, based on our previous works on the synthesis of azaheterocyclic compounds, [15] we chose N ‐propargyl‐C‐2‐substituted‐pyrroles as the starting material, synthesized as described in our previous report [16a–e] . Reaction of 13a with a base provided the indolizine derivative 15a in relatively good yield beside the allene 16 and the hydrolysis compound 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, AuBr 3 did not yield as much product as AuCl 3 (entry 7), indicating that the counter-anion is also crucial for cyclization. 15a Solvent screening showed that the most suitable solvent was EtOH (entries 16–21); other polar aprotic or aromatic solvents did not give a superior yield to EtOH. TLC screening indicated the optimal temperature and time were the EtOH reflux temperature and 18 hours, respectively (entry 15).…”
Section: Table 1 Optimization Of Reaction Conditions Fo...mentioning
confidence: 99%